Fort Benning Blues - Busby, Mark (Book collections on Project MUSE., 2001)
Jeff Adams, drafted in 1969, faces a war he doesn't understand. The product of a patriotic Texas family, he knows he could never face his grandfather, the first Jefferson Bowie Adams, if he dodges the draft, so, to buy some time, he volunteers for Officer Candidate School in Fort Benning, Georgia.